A sustainable one-step strategy for highly graphitized capacitive carbons with hierarchical micro–meso–macro porosity. Issue 5 (9th February 2022) - Liu, Huili; Su, Suisui; Wang, Heng; Wang, Miaomiao; Zhang, Shouren; Chang, Binbin; Yang, Baocheng
Abstract : Highly graphitized porous carbons with hierarchical micro–meso–macropores were prepared by a simple, one-step, sustainable strategy. Abstract : Large micropore surface area, superior electrical conductivity and suitable pore size are simultaneously desired characteristics for high-performance capacitive carbons. However, these desired features tend to be mutually competing, and are generally difficult to integrate into a single carbon. Considering this challenge, we developed a sustainable, less time-demanding, pollution-free strategy to construct highly graphitized porous carbon (GPC) by one-step heat-treatment. This approach achieves the need of the abovementioned characteristics for capacitive carbons, wherein potassium ferrate works as both an activating agent and graphitization catalyst to achieve synchronous hierarchical porosity and graphitization of wasted natural wood, and the resultant carbon materials possess a large micropore surface area of 870.4 m 2 g −1, a highly graphitic carbon skeleton and a well-interconnected micro–meso–macropore structure. The assembled GPC-based symmetrical capacitors exhibited a satisfactory capacitive performance in different aqueous electrolytes (H2 SO4, KOH and Na2 SO4 ), including high specific capacitance, prominent rate capability, satisfactory energy density and good cycle stability. Meanwhile, we compared the contributions of porosity and the graphitized structure to capacitive performance, and porosity was dominant in determining capacitance and the graphitized skeleton had a positive effect in enhancing the capacitive performance. In addition, we established the relationship between the structure of GPC and electrochemical capacitive performance in different aqueous electrolytes, providing a valuable reference for GPC-based supercapacitors in different practical applications. More importantly, this strategy holds great promise to sustainably convert biowaste to high-added-value capacitive carbons for advanced energy storage applications in the future.